DNA barcoded competitive clone-initiating cell analysis reveals novel features of metastatic growth in a cancer xenograft model. Issue 3 (22nd July 2022) - Aalam, Syed Mohammed Musheer; Tang, Xiaojia; Song, Jianning; Ray, Upasana; Russell, Stephen J; Weroha, S John; Bakkum-Gamez, Jamie; Shridhar, Viji; Sherman, Mark E; Eaves, Connie J; Knapp, David J H F; Kalari, Krishna R; et al.
Abstract: A problematic feature of many human cancers is a lack of understanding of mechanisms controlling organ-specific patterns of metastasis, despite recent progress in identifying many mutations and transcriptional programs shown to confer this potential. To address this gap, we developed a methodology that enables different aspects of the metastatic process to be comprehensively characterized at a clonal resolution. Our approach exploits the application of a computational pipeline to analyze and visualize clonal data obtained from transplant experiments in which a cellular DNA barcoding strategy is used to distinguish the separate clonal contributions of two or more competing cell populations. To illustrate the power of this methodology, we demonstrate its ability to discriminate the metastatic behavior in immunodeficient mice of a well-established human metastatic cancer cell line and its co-transplanted LRRC15 knockdown derivative. We also show how the use of machine learning to quantify clone-initiating cell (CIC) numbers and their subsequent metastatic progeny generated in different sites can reveal previously unknown relationships between different cellular genotypes and their initial sites of implantation with their subsequent respective dissemination patterns. These findings underscore the potential of such combined genomic and computational methodologies to identify new clonally-relevant drivers of site-specific patterns of metastasis. Graphical Abstract: